Factors Influencing The Quality of Construction Projects in Public Universities - Aenet , Yohanes; Maniha, Naruka (International Journal of Business, Management and Economics, 2023)
The study aims to determine factors affecting project quality in public universities in eastern Ethiopia. The researchers used primary data in a quantitative research approach to accomplish the objectives. The dependent variable, project quality, is regressed on five Explanatory variables: Leadership, Policy & Strategy, People, Partnership & Resources, and Process. Each of these characteristics was gathered from the consultant, client, and contractor. In order to determine the validity of the model. All multiple regression assumption tests were found to be valid. According to regression analysis, it was found that Leadership, Policy & Strategy, People, Partnership & Resources, and Process all have a substantial impact on project quality. The analysis from one-way ANOVA revealed that clients, contractors, and consultants have similar perceptions of the five quality attributes, leadership, people and policy and strategy, partnership and resources and process. Results from this research can be used by construction firms to improve their quality management systems, as they will indicate where the emphasis should be focused to ensure the ongoing improvement of project quality and sustainability.